A Handbook of Statistics and Quantitative Analysis for Educational Leadership - Mulcahy, John W. (University Press of America, 2009)
This handbook is an approachable reference for all levels of educational leadership. The topics are presented with a clarity that makes the mathematics accessible, even if the reader has not had prior training in research methods or statistics.
Keywords: School management and organization; Statistical methods; Statistical methods; Educational leadership; dept.edl; faculty_collection

Curriculum Alignment: Research-Based Strategies for Increasing Student Achievement - Squires, David A. (Corwin Press, 2009)
Keywords: Curriculum planning; Standards; United States; United States; Education; United States; Educational accountability; United States; Educational tests and measurements; dept.edl

Aligning and Balancing the Standards-Based Curriculum - Squires, David A. (Corwin Press, 2005)
Keywords: Curriculum planning; Standards; United States; United States; Competency-based education; United States; Education; dept.edl; faculty_collection

The Power of Poetry for School Leadership: Leading with Attention and Insight - Richardson, Lystra M. (Scarecrow Press, 2003)
Keywords: Poetry; Study and teaching; United States; United States; Educational leadership; dept.edl; faculty_collection

New Pythian Voices: Women Building Political Capital in Ngos in the Middle East - Magno, Cathryn S. (Routledge, 2002)
Keywords: Middle East; Middle East; Feminism; Middle East; Non-governmental organizations; Political activity; Women; dept.edl; faculty_collection

Imaging girls: visual methodologies and messages for girls' education - Magno, Cathryn; Kirk, Jackie (Compare, 2008)
This article describes the use of visual methodologies to examine images of girls used by development agencies to portray and promote their work in girls' education, and provides a detailed discussion of three report cover images. It details the processes of methodology and tool development for the visual analysis and presents initial 'readings' of the selected images. This initial study highlights the relevance of image analysis to the field of gender, education and development and of critical reflection on the different messages and meanings inherent in images of girls and girls' education which relate to complex questions of power and privilege, position and post-coloniality. The authors recommend that within development agencies education and communication specialists work together to develop more sophisticated processes for image selection, review and feedback, and that researchers in the field further engage with visual methodologies to inform current theories of girlhood, education, schooling and empowerment.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-326-190-434-512 tex.type: [object Object]
Keywords: Education; Girls; Images; Methodology; Representation; dept.edl

Teaching in transition: Examining school-based gender inequities in central/southeastern Europe and the former Soviet Union - Magno, Cathryn; Silova, Iveta (International Journal of Educational Development, 2007)
In the last decade, gender equity has become one of the most prominent issues in education reform efforts worldwide. Yet, questions of gender equity have received very little attention in the education reform efforts in the post-socialist countries during the transition period. Focusing on the political, economic, and social changes of the 1990s, this article examines school-based gender equity as it is treated in textbooks, curriculum, teacher attitudes, school environment, leadership and tracking. The article presents gender-sensitive strategies for reform and explores how existing `genderneutral' education practices detrimentally affect gender equity in schools, providing country-specific examples. The article concludes with recommendations for teaching in transition, given the education sphere's strong potential to redress gender inequities. (c) 2006 Elsevier Ltd. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/134-656-786-395-500 tex.unique-id: [object Object]
Keywords: Education reform; Eurasia; Europe; Gender equity; Post-socialist transition curriculm; curriculum; dept.edl; education reform; equity; gender disparity; gender relations; gender role; peer-reviewed; post-communism; social change; teaching; transitional economy